TANTANGAN SISTEM KOMUNIKASI LAUT DI INDONESIA SEBAGAI FAKTOR PENDUKUNG KESELAMATAN PELAYARAN - Aulia Windyandari (TEKNIK, 2011)
Shipping safety topics lately skyrocketed in the surface and became a hot news, both print and electronic media,along with marine accidents which occurred in late 2006 and early 2007. The role of shipping safety in marinetransportation system is essential for this type of transport is reflected as full-tinged danger and threat of storms,fog, and the movements of the sea as waves, currents, sea corals, sedimentation and cruise lines are fixed andchanged. That’s why our shipping have very high risk, and therefore the safety aspects must be absolutelyguaranteed.Therefore necessary communication equipment that support the safety of the ship sailing. Due to sophisticatedcommunications equipment on board, will reduce the number of ship accidents and casualties in the case ofaccident in shipping.